The association between red blood cell and platelet transfusion and subsequently developing idiopathic pneumonia syndrome after hematopoietic stem cell transplantation. Issue 4 (27th August 2013) - Vande Vusse, Lisa K.; Madtes, David K.; Guthrie, Katherine A.; Gernsheimer, Terry B.; Curtis, J. Randall; Watkins, Timothy R.
<x xml:space="preserve">Abstract</x> Background Blood transfusions are common during hematopoietic stem cell transplantation (HSCT) and may contribute to lung injury. Study Design and Methods This study examined the associations between red blood cell (RBC) and platelet (PLT) transfusions and idiopathic pneumonia syndrome (IPS) among 914 individuals who underwent myeloablative allogeneic HSCT between 1997 and 2001. Patients received allogeneic blood transfusions at their physicians' discretion. RBCs, PLTs, and a composite of "other" transfusions were quantified as the sum of units received each 7‐day period from 6 days before transplant until IPS onset, death, or Posttransplant Day 120. RBC and PLT transfusions were modeled as separate time‐varying exposures in proportional hazards models adjusted for IPS risk factors (age, baseline disease, irradiation dose) and other transfusions. Timing of PLT transfusion relative to myeloid engraftment and PLT ABO blood group (match vs. mismatch) were included as potential interaction terms. Results Patients received a median of 9 PLT and 10 RBC units. There were 77 IPS cases (8.4%). Each additional PLT unit transfused in the prior week was associated with 16% higher IPS risk (hazard ratio, 1.16; 95% confidence interval, 1.09‐1.23; p < 0.001). Recent RBC and PLT transfusions were each significantly associated with greater risk of IPS when examined without the other; only PLT transfusions retained significance when both exposures were included in the model. The PLT association was not modified by engraftment or ABO mismatch. Conclusion PLT transfusions are associated with greater risk of IPS after myeloablative HSCT. RBCs may also contribute; however, these findings need confirmation.